The Role of Birth Certificates in the Population Administration System for Children in Indonesia - Hafidati, Putri (International Journal of Business, Law, and Education, 2025)
Parents must record the birth of their child, as it is a legal requirement for citizens to have their births registered. By the applicable Law, this recording is carried out through a specific procedure and archived in a sheet that is then known as the "Birth Certificate". This birth certificate marks the beginning of a person's registration in the eyes of the Law in Indonesia. A child needs a status that is listed on a birth certificate, indicating that he is a legal child of parents whose names are also listed on the birth certificate. The purpose of this research is to find out and analyze the implementation of the policy of issuing Birth Certificates and the factors that are obstacles to the implementation of the policy of issuing Birth Certificates. This research method is normative because it is the starting point of existing legal regulations. Research Results: Many couples still do not have a marriage book (Nikah Siri). Marriage under the hand is still not recognized by formal Law because it is not recorded in the KUA or Civil Registry. Not recording the marriage will have an impact on the status of the child, because it will be considered a child out of wedlock, meaning that the child does not have a legal relationship with his father. Children resulting from serial marriages or outside of legal marriage can indeed obtain a birth certificate